Effects of Cryptocaryon irritans infection on the histopathology, oxidative stress, immune response, and intestinal microbiota in the orange-spotted grouper Epinephelus coioides - Zeng, Shimin; Duan, Yafei; Li, Xiong; Hu, Yingtong; Mo, Zequan; Dan, Xueming; Li, Yanwei (Fish & shellfish immunology, 2023)
Cryptocaryon irritans is a parasitic ciliate of marine fish, causing serious mortality and economic loss of grouper. In this study, the orange-spotted grouper (Epinephelus coioides) were separately exposed to C. irritans infection for 72 h at a dose of 5000 or 10000 active theronts per fish, and we evaluated the changes in histopathology, oxidative stress, immune response, and intestinal microbiota composition. The results showed that C. irritans infection caused pathological alteration on the skin, gills, and liver of E. coioides. Oxidative stress responses occurred in the liver and gills, reflected in the corresponding antioxidant enzyme and gene indexes. The mRNA expression levels of inflammation-related genes (IL-1β, IL-6, and IL-8) and the mediators of apoptosis (casp3, casp9, and cytc) were increased in the liver and gills of the fish. C. irritans infection also affected the diversity and composition of intestinal microbiota. Specifically, the relative abundance of Firmicutes was increased, whereas that of Proteobacteria was decreased. Several potentially beneficial bacteria (Pandoraea, Clostridium sensu stricto 1, Christensenellaceae R-7 group, and Weissella) were decreased, whereas pathogenic bacteria (Streptococcus and Acinetobacter) were increased. In conclusion, this study reveals that C. irritans infection caused histopathology, immune disorders, and intestinal microbial community variation in E. coioides. •C. irritans infection caused pathological alteration in the skin, gills and liver of E. coioides.•C. irritans infection caused oxidative stress, inflammation and apoptosis in the liver and gills of E. coioides.•C. irritans infection altered the diversity and composition of intestinal microbiota of E. coioides.